Performance of integral bridge with various span lengths - Tuan Abdul Manaf, Tuan Khusairry (2014)
An integral bridge may be defined as having no expansion joints or sliding bearings, the deck is continuous across the length of the bridge. Among the advantages of this type of bridge is reducing the cost of maintenance and bringing comfort to road users as there is no connection between the superstructure and substructure. However, this type of bridge is quite different in comparison to the conventional bridge in terms of the analysis and design. The aim of this study is to examine the performance, with respect to the terms of reference of the PWD Bridge Unit of integral bridges in excess of 60 m span length. This study is also intended to investigate and make a comparison between integral bridges with various span lengths in terms of the performance particularly for the reactions resulting from the applied load. A series of integral bridges with different span configurations and lengths have been designed and analyzed using STAAD Pro. The results show that when the span increases, the values of hogging moments at connection between beam and pier increase significantly. From the analysis and design that have been made, it can be concluded that for integral bridges with lengths more than 70 m (for example, configuration of bridge of 20m + 40m + 20m), the bridge can be designed as an integral bridge but the thickness of the deck slab should be increased in order to sustain the resulting negative hogging moment on the connections between the beams and piers. However, the cost incurred due to increasing the thickness of the deck slab should be calculated in order to assess whether a bridge should designed as an integral bridge or conventional bridge.